Translanguaging/trans-semiotizing in teacher-learner interactions on social media: Making learner agency visible and achievable. (February 2022) - Chen, Yanyan; Zhang, Ping; Huang, Lu
Abstract: Through a translanguaging lens, trans -semiotizing emphasizes the entanglement of language and other semiotic resources to negotiate meaning. Recent studies have begun to recognize the pedagogical functions of translanguaging/ trans -semiotizing by optimizing the use of multisemiotic resources. The present study contributes to this growing body of literature by exploring the association between translanguaging/ trans -semiotizing and learner agency (the initiative to learn) in a course of content and language integrated learning (CLIL) under everyday and crisis contexts. Firstly, the patterns of trans -semiotizing were analyzed in social media interactions between 2121 undergraduate students and three teachers over three semesters. Secondly, the process of trans -semiotizing for learner agency was examined through multimodal conversation analysis. Thirdly, perceptions of four semiotic resources were explored via chat-log-stimulated interviews and a follow-up questionnaire. The convergent results show that trans-semiotizing was a common practice under both everyday and crisis contexts, being closely associated with the fluctuation of learner agency. Significantly, trans-semiotizing between texts and pictures fosters learner agency by facilitating learners' exploration of the learning opportunities, while trans-semiotizing to emojis manifests the fluctuant learner agency. These findings indicate that trans-semiotizing makes learner agency more visible and achievable, and teachers' trans-semiotic competence to differentiate and deploy multisemiotic resources is critical.